Molecular Imaging of Biological Samples on Nanophotonic Laser Desorption Ionization Platforms. Issue 14 (1st March 2016) - Stopka, Sylwia A.; Rong, Charles; Korte, Andrew R.; Yadavilli, Sridevi; Nazarian, Javad; Razunguzwa, Trust T.; Morris, Nicholas J.; Vertes, Akos
Abstract: Mass spectrometry imaging (MSI) is a comprehensive tool for the analysis of a wide range of biomolecules. The mainstream method for molecular MSI is matrix‐assisted laser desorption ionization, however, the presence of a matrix results in spectral interferences and the suppression of some analyte ions. Herein we demonstrate a new matrix‐free MSI technique using nanophotonic ionization based on laser desorption ionization (LDI) from a highly uniform silicon nanopost array (NAPA). In mouse brain and kidney tissue sections, the distributions of over 80 putatively annotated molecular species are determined with 40 μm spatial resolution. Furthermore, NAPA‐LDI‐MS is used to selectively analyze metabolites and lipids from sparsely distributed algal cells and the lamellipodia of human hepatocytes. Our results open the door for matrix‐free MSI of tissue sections and small cell populations by nanophotonic ionization. Abstract : Weight and see : A matrix‐free mass spectrometry imaging technique uses nanophotonic ionization based on laser desorption ionization from a highly uniform silicon nanopost array. In mouse‐brain and kidney tissue sections, the distributions of over 80 molecular species could be determined with 40 μm spatial resolution.